Studi Pengaruh Suhu dan Waktu Reaksi Pada Sintesis α-Terpineol Dari Terpentin Dengan Menggunakan Katalis Asam Trikhloroasetat - Ulfah Nur Khikmah; Herti Utami (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Turpentine contains α-pinene the main component of about 75-85% and the rest consists of β-pinene (2-3%), champhene (4-15%), and limonene (5-15%). The content of α-pinene as the largest component in turpentine oil can be increased its selling value by hydration reaction to produce α-terpineol. The purpose of this study is to determine the effect of temperature and reaction time to the conversion α-pinene and selectivity a-terpineol in the synthesis of a-terpineol from turpentine by using trichloroacetic acid catalyst. The variables studied were temperature at 55, 65, and 75oC; and reaction time of 30, 60, 120, and 240 minutes, respectively. The reaction was carried out in a three-neck glass equipped with a heater, a thermometer, and a magnetic stirrer. The method of this study was hydration reaction by reacting 0.055 mol turpentine, 0.55 mol aquadest, and 0.32 mol trichloroacetic acid catalyst with a stirring speed of 385 rpm. The analysis of the synthesis was accomplished using Gas Chromatography Method to determine the α-pinene and α-terpineol concentrations obtained, and Gas Chromatography-Mass Spectroscopy to recover the compounds contained in the sample. The optimum condition was obtained at the temperature of 65oC and reaction time of 60 minutes with α-pinene conversion obtained 96,293% and the selectivity of α-terpineol 34,429%.